Characterization of Phytophthora spp. and application of rhizobacteria with biocontrol potential in black pod disease in Theobroma cacao variety CCN-51 - Cedeño Moreira, Ángel Virgilio (2020)
The objective of the work focused on characterizing the biodiversity of Phytophthora spp. and rhizobacteria with potential for biocontrol in black pod disease in CCN-51. Nine plant samples with symptoms of the disease were collected from cocoa-producing areas, evaluating their morphological characteristics and identification by PCR. Different morphotypes of colonies are observed: cottony, regular and starry edge characteristic for Phytophthora spp. Electrophoresis profiles reveal an amplicon of 159 bp for P. palmivora, demonstrating its distribution in the nine zones. The tests on mycelial inhibition in vitro to P. palmivora, determined high levels of antagonism of 78 and 60% by direct confrontation with the rhizobacteria. These results in bio-protection to CCN-51 by applications of P. veronii R4, A. calcoaceticus BMR2-12, S. marcescens PM3-8 and P. protegens CHA0 are effective in the control of P. palmivora strain (BL15), without the application of bacteria the disease progress is evidenced at the level foliar at 15 and 19 dpi with (2.00E + 05) zoospores. The edaphic application of rhizobacteria in CCN-51, the promoter capacity to plant growth and suppression of P. palmivora disease.